2013
DOI: 10.1007/s10803-013-1830-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Risk Markers for Sleep Disturbance in Participants of the Autism Treatment Network

Abstract: We explored possible cognitive, behavioral, emotional, and physiological risk markers for sleep disturbance in children with autism spectrum disorders. Data from 1,583 children in the Autism Treatment Network were analyzed. Approximately 45 potential predictors were analyzed using hierarchical regression modeling. As medication could confound findings, it was included in the analyses as a covariate. Results revealed that anxiety, autism symptom severity, sensory sensitivities, and GI problems were associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 47 publications
4
116
2
Order By: Relevance
“…Hollway et al (2013) found that there were more sleep problems in children who had regressed that those who had no developmental regression. Hansen et al (2008) reported no significant differences were found between the children with or without regression in terms of sleep problems.…”
Section: Developmental Regressionmentioning
confidence: 96%
See 4 more Smart Citations
“…Hollway et al (2013) found that there were more sleep problems in children who had regressed that those who had no developmental regression. Hansen et al (2008) reported no significant differences were found between the children with or without regression in terms of sleep problems.…”
Section: Developmental Regressionmentioning
confidence: 96%
“…Therefore the fewer hours slept, the more severe were the symptoms of autism. Hollway et al (2013) found that the core symptoms of autism and autism subtype predicted sleep quality in children with ASD.…”
Section: Autism Severity Sleep Problems In Autism Spectrum Disordermentioning
confidence: 98%
See 3 more Smart Citations